A study protocol for a therapist guided digital cognitive-behavioral therapy for children with avoidant/restrictive food intake disorder and their parents - Engelkamp, Julia E.; Koeder, Lara-Marie; Dalholf, Manuela; Thomas, Jennifer J.; Eddy, Kamryn T.; Hartmann, Andrea S. (Frontiers in Psychiatry, 2026)
BackgroundAvoidant/restrictive food intake disorder (ARFID) is an eating disorder prevalent in children and associated with several health and psychosocial impairments. Despite its prevalence, limited treatment services are available and children with ARFID often do not receive specialized care. Cognitive-behavioral therapy has shown feasibility in face-to-face trials supporting proof-of-concept. Digital interventions could increase treatment accessibility in this population.MethodsIn a single-armed intervention trial (N = 40) children aged 8–14 years with a primary diagnosis of ARFID and their caregivers will receive a digital cognitive-behavioral therapy. The intervention consists of a 12-session program, combining video therapy sessions with children and caregivers and self-guided modules. Assessments occur at baseline, mid-treatment, post-treatment, and 4-week follow-up with additional symptom monitoring questionnaires per session. Primary outcomes include feasibility, recruitment and retention rate. Secondary outcomes include ARFID symptoms (e.g., Eating Disorder Examination ARFID module, Nine Item Avoidant/Restrictive Food Intake Disorder screen), food neophobia (Food Neophobia Scale) and quality of life (Generic Quality of Life Instrument for Children-Revised).DiscussionThis study evaluates the feasibility and proof of concept of a therapist-guided digital intervention for ARFID. If feasible and acceptable, the digital intervention may help to increase treatment access for children with ARFID in German-speaking countries. Furthermore, findings can inform future larger-scale randomized control trials and the development of digital interventions for ARFID.Clinical Trial Registrationhttps://drks.de/search/de/trial/DRKS00038026/details, identifier DRKS00038026.